Inovasi dalam Manajemen Kurikulum untuk Menghadapi Era Digital - Sugianto, Endrik (TSAQOFAH, 2024)
This research aims to identify innovations in curriculum management needed to face the challenges of the digital era through a literature study method. In the digital era, the integration of technology in the learning process has become a necessity to improve educational effectiveness. This study reviews various literatures that discuss innovative approaches in planning, implementing and evaluating technology-based curriculum. The results show that the use of educational technology, such as e-learning, digital platforms and project-based learning, can improve student engagement and learning effectiveness. In addition, continuous training for teachers to master the latest technologies and curriculum adjustments to suit the needs of industry 4.0 are required.